CARDIAC RADIOGRAPHICAND ELECTROCARDIOGRAPHIC PARAMETERSINTHEPERUVIAN HAIRLESS DOG - Carrillo V., Lyn (2011)
The objective of the study was to determine radiographic and electrocardiographicparameters in individuals of the Peruvian Hairless Dog breed, median size, in Lima, Peru.Thirty adult animals of both sexes, 8-12 kg body weight, and clinically healthy were used.An electrocardiographic evaluation was conducted using the six standardelectrocardiographic leads and waves (P, QRS and T), segments (PR, QRS and QT) andrhythm (normal sinus and sinus arrhythmia). A radiographic evaluation was performedwith lateral and ventrodorsal/dorsoventral projections to determine the cardio vertebralratio (VHS) and total cardiac expansion (RTCE). The cardiac radiographic and electrocardiographic parameters were within the values for dogs in general. Sex had noinfluence on the studied parameters. The frequency of sinus arrhythmia starts from 4years of age.